2018
DOI: 10.1021/acs.jpca.8b09068
|View full text |Cite
|
Sign up to set email alerts
|

Bending Ternary Dihalides

Abstract: The bonding preferences in the mixed dihalides (MXY) of groups 2 and 12 metals, including the extent of any anomalous bending, are assessed and established. The deviation from linearity in group 2 metal binary dihalides is well-known, runs contrary to simple bonding models, and is believed to be decisive for structural preferences in the extended solids. Yet the bonding in the ternary, MXY, molecules has not been investigated systematically until now. The structure and bonding in these ternary systems (and, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
(102 reference statements)
0
6
0
Order By: Relevance
“…We suggest that some off-linear metal−ligand bond angles in ruthenium and rhodium complexes can be explained with this model. We anticipate that, with similar reasoning, angles can be understood in asymmetric triatomic molecules (examples by Prasad et al 42 ), in molecules with different electronic excited or charged states, and in weakly bonded systems (examples by Remko 43 ). We showed in previous work that also the geometry of ring structures can be rationalized.…”
Section: ■ Introductionmentioning
confidence: 67%
“…We suggest that some off-linear metal−ligand bond angles in ruthenium and rhodium complexes can be explained with this model. We anticipate that, with similar reasoning, angles can be understood in asymmetric triatomic molecules (examples by Prasad et al 42 ), in molecules with different electronic excited or charged states, and in weakly bonded systems (examples by Remko 43 ). We showed in previous work that also the geometry of ring structures can be rationalized.…”
Section: ■ Introductionmentioning
confidence: 67%
“…The faculty published 2 peer‐reviewed books, [ 238,239 ] 9 peer‐reviewed book chapters, [ 240–248 ] and 115 peer‐reviewed research papers. [ 249–363 ] This comes to 1.6 peer‐reviewed products/faculty/year during the 3‐year grant period, which is 3.2 times the rate of publication for natural science faculty at PUIs. [ 46 ]…”
Section: Research Accomplishments (Intellectual Merit) and Transformamentioning
confidence: 99%
“…Kelling Donald's research: In the Donald research group, work is focused on (a) halogen bonding and other sigma hole interactions in organic and inorganic systems, [ 210,278 ] (b) fluxionality in planar inorganic clusters and the nature and potential control of so‐called molecular machines, [ 208,263 ] (c) the evolution of structural preferences and thermal stability in metal halide and hydride molecules, clusters, and corresponding extended solids, [ 322 ] (d) the stability and catalytic applications of structurally interesting or unusual main‐group and transition‐metal organometallic compounds, [ 151,231,351,385 ] (e) the stabilization of unusual bonding arrangements, including planar tetra‐coordinate and other unusual coordination environments, [ 172 ] (f) quantifying currently qualitative but transferrable concepts in chemical bonding, [ 233 ] and (g) aromaticity and analogous phenomena in non‐hydrocarbon systems. [ 338,386 ] The MRI resources are essential for calculations on large and heavy elemental systems.…”
Section: Overview Of Mercury Faculty Research Effortsmentioning
confidence: 99%
“…The mercury dihalides are an intriguing series of compounds in which relativistic effects and competing weak electrostatic, covalent, and ionic contributions in chemical bonding collide. It is now well accepted that in the gas phase , all of the simple mercury dihalide molecules (Hg X 2 for X = F, Cl, Br, and I) are linear. , It can be difficult to establish linearity unambiguously for simple triatomic molecules in matrix isolation studies, especially if the potential energy surface is flat (i.e., where the barrier to bending is very low), , but state-of-the-art computational investigations (and reliable electron diffraction data, where available) affirm in fact that all of the binary and ternary mercury dihalides (Hg XY ; for X = Y, and X ≠ Y ) are linear. , …”
Section: Introductionmentioning
confidence: 99%
“…But that kind of s–d orbital mixing is not achievable for Hg XY systems, because the ( n – 1) d subshell (i.e., the set of 5d orbitals) is completely filled in Hg. That general unavailability of empty and easily accessible frontier d orbitals in Hg (and in Zn and Cd in group 12) helps to account thus for the rigidity of their linear dihalide molecules. , Indeed, a number of different research groups have shown that Hg X 2 molecules are so rigid that their dimers (Hg X 2 ) 2 feature no intermonomer covalent bondingsimply Hg X 2 monomers held together by weak electrostatic interactions in loose pairs. , And, remarkably, this characteristic of weak intermonomer interactions persists all the way through to the extended solids in some cases, but not allwith HgF 2 being the prominent exception. …”
Section: Introductionmentioning
confidence: 99%